HYBRID LEARNING TIME MODIFICATION CAN IMPROVE LEARNING ACTIVITY AND LEARNING OUTCOMES - Umi Kulsum (Universitas Negeri Medan, 2021)
The purpose of this study was to determine the effectiveness of hybrid learning time modification in terms of learning outcomes; knowing the relationship between learning activities and learning outcomes and knowing the effect of hybrid and one other group is the conventional group (face-to-face only), this group is the control group.Collecting data using a learning activity questionnaire and a knowledge test to determine learning outcomes. Data analysis technique with Ancova. The results of the study: (1) hybrid learning time modification is effective in improving learning outcomes (2) significant relationship between learning activity and learning outcomes, significance 0.000; (3) there is a significant difference in the effect of variations in hybrid learning time modification on learning activity and learning outcomes, the significance of 0.037Keywords: Time Modification, Hybrid Learning, Active Learning, Learning Outcomes